College communication - Camp, Sue C.; Satterwhite, Marilyn L. (Glencoe McGraw-Hill, 1998)
This soft-cover business communication text -- an abridged version of College English and Communication, 7e -- retains that text's strong features but lacks the heavy emphasis on grammar and mechanics. Instead, College Communication focuses on the development of effective listening, speaking, and writing skills. Emphasis is on the global, ethical, technological, and customer service aspects of communication.